2008
DOI: 10.1103/physrevb.78.094101
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical trend of ion exchange ability with divalent cations in hydroxyapatite

Abstract: First-principles calculations are performed for hydroxyapatite ͑Hap͒ in order to investigate the relative ion exchange ability with divalent cations such as Mg 2+ , Ni 2+ , Cu 2+ , Zn 2+ , Sr 2+ , Cd 2+ , Ba 2+ , and Pb 2+. Their ionic substitutional energies are calculated from total energies of supercells and chemical potentials for Ca 2+ and the foreign cations determined under chemical equilibrium between HAp and its saturated solution. It is found that, in most cases, the ion exchange ability is basically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 40 publications
5
57
0
Order By: Relevance
“…In this regard, however, details were already described in our preceding papers [23][24][25]. Therefore, only some important points are briefly described as follows.…”
Section: Defect Formation Energiesmentioning
confidence: 95%
See 1 more Smart Citation
“…In this regard, however, details were already described in our preceding papers [23][24][25]. Therefore, only some important points are briefly described as follows.…”
Section: Defect Formation Energiesmentioning
confidence: 95%
“…Since the concentration of M 2+ has to be set to a particular value, the value of 10 À3 mol=l was used in this study. The concentrations of Ca 2+ ions were evaluated from experimental values of the solubility constant of TCP, the acid dissociation constants of phosphate ions, the ionic product of water, and total charge neutrality in the solution [24]. When a pH (=Àlog [H + ]) is taken as a variable, ionic concentrations in the saturated solution are obtained as a function of pH as displayed in Fig.…”
Section: Chemical Potentials In Chemical Equilibrium With Aqueous Solmentioning
confidence: 99%
“…For instance, the preferential incorporation of Zn 2+ and Pb 2+ into the Ca(II) site of apatites has been demonstrated using Zn K-edge EXAFS and XANES, [25] and 207 Pb solid state NMR, [26] respectively. Furthermore, an increasing number of computational studies are reported aimed at determining any energetic advantages of incorporating impurity ions into different sites of the HA lattice, [27][28][29][30] and it has been shown that these can bring further insight into the structural changes in substituted species, and help understand spectroscopic data. [25] In the case of Mg-substituted apatites, no experimental NMR or XAS data have been reported so far, and the first computational studies were published very recently.…”
Section: Introductionmentioning
confidence: 99%
“…However, this was not the case. The physical reason behind this observation could be attributed to the electronic structure of Pb 2+ ions [47]. The theoretical electronic structure calculations indicate that in the atom-projected density of states curves, the Pb 2+ ions have active 6s 2 lone-pair electrons that hybridize with oxygen 2p electrons resulting in a strong covalent bond formation.…”
Section: Low-dimensional Plotsmentioning
confidence: 99%